Role of environment policy and community participation on air pollution control in Malaysia:lessons from Japan. - Mohamed, Abdul Rahman (Universiti Sains Malaysia, 2004)

(untitled)
Air pollution is defined as the presence of pollutant in the air, in quantities large enough to produce harmful effect towards human health, vegetation, human property and water ground cycle.